RHOA/ROCK PATHWAY PARTICIPATES IN THE STUDY OF RELATED MECHANISMS OF APATINIB IN THE TREATMENT OF BREAST CANCER-INDUCED HYPERTENSION. (June 2022) - Wang, Wenjuan; Zhan, Haodong; Wang, Qiongying; Zhuang, Chenchen; Li, Caie; Fan, Xin; Qi, Miaomiao; Sun, Runmin
Abstract : Objective: To explore activation of the RhoA/ROCK pathway whether involved in the mechanism of apatinib in the treatment of breast cancer-induced hypertension and whether ROCK pathway inhibitors can prevent and reverse the increase in blood pressure and target organ damage caused by apatinib in the treatment of breast cancer, thus confirming its therapeutic effect on this type of hypertension. Design and method: Thirty female Balb/c nude mice aged 4–6 weeks and the human breast cancer cell MDA-MB-231 were used for breast cancer tumorigenesis. Mice were randomly divided into 5 groups, each with 6 mice; 1): no tumor model, 2): just tumor model; 3): high-salt diet (giving customized 8% high-salt feed); 4) apatinib 50 mg/kg.d; 5): apatinib 50 mg/kg. d + Y27632 10 mg/kg. d. After the tumor grew to the target volume of 100–150mm3, intervention was performed for 3 weeks, blood pressure was measured weekly, and body weight was measured every day. Results: 1. The blood pressure of the fourth group was higher than other groups. 2. The ventricular thickness of the mice in the third and fourth groups was thicker than the first and second groups, and the fifth group was less than the fourth group. 3. Masson staining of mice aorta from strong to weak is: the fourth group, the third group, the fifth group, the second group, the first group. 4. The results of mice aortic mRNA and Western Blot showed that RhOA and ROCK1 in the third, fourth, and fifth groups were higher than those in the first and second groups, and the fifth group was lower than the fourth group. 5.The mice aortic immunohistochemistry show that the third and fourth groups of COLI and COLIII are higher than the first and the second group, the fifth group has a lower than the fourth group. Conclusions: The RhoA/ROCK pathway is involved in the apatinib-induced hypertension. After applying apatinib to breast cancer, the blood pressure, the vascular stiffness, the Endothelin-1, RhoA/ROCK pathway protein and mRNA are increased, the endothelial function decreased, and RhoA/ROCK pathway inhibitors can prevent and reverse the changes by apatinib.